La participación femenina en los mercados de trabajo urbanos en México : 1970-1980 - Oliveira, Orlandina de (El Colegio de México A.C., 1989)
In this article we analyze the presence of women in urban labor markets in Mexico in the 1970s. Initially, on the basis of an examination of rates of participation in the economy taken from the population censuses of 1970 and 1980, we identify urban areas with 100,000 or more inhabitants which are characterized by high and low levels of female and male economic activity. Then, we center our attention on female labor in order to draw up two typologies for cities. The first one, constructed on the basis of specific rates of participation by age, allows us to pinpoint urban areas that make the greatest use of young labor and those that absorb adolescent and adult workers. The second typology, based on the insertion of women in the work force, is useful for classifying urban areas according to the diversification of their labor markets. We found that, in general, women participate mostly in diversified labor markets that absorb labor from different age groups and with different levels of skills, and that the presence of women is not necessarily greater in the more dynamic cities, in economic terms, which have more male participation.